A Structurally Characterized Organometallic Plutonium(IV) Complex. (30th March 2017) - Apostolidis, Christos; Walter, Olaf; Vogt, Jochen; Liebing, Phil; Maron, Laurent; Edelmann, Frank T.
Abstract: The blood‐red plutonocene complex Pu(1, 3‐COT′′)(1, 4‐COT′′) (4 ; COT′′=η 8 ‐bis(trimethylsilyl)cyclooctatetraenyl) has been synthesized by oxidation of the anionic sandwich complex Li[Pu(1, 4‐COT′′)2 ] (3 ) with anhydrous cobalt(II) chloride. The first crystal structure determination of an organoplutonium(IV) complex revealed an asymmetric sandwich structure for4 where one COT′′ ring is 1, 3‐substituted while the other retains the original 1, 4‐substitution pattern. The electronic structure of4 has been elucidated by a computational study, revealing a probable cause for the unexpected silyl group migration.